2010
DOI: 10.1364/oe.18.024770
|View full text |Cite
|
Sign up to set email alerts
|

High sustained average power cw and ultrafast Yb:YAG near-diffraction-limited cryogenic solid-state laser

Abstract: We report what we believe to be record performance for a high average power Yb:YAG cryogenic laser system with sustained output power. In a CW oscillator-single-pass amplifier configuration, 963 W of output power was measured. In a second configuration, a two amplifier Yb:YAG cryogenic system was driven with a fiber laser picosecond ultrafast oscillator at a 50 MHz repetition rate, double-passed through the first amplifier and single-passed through the second, resulting in 758 W of average power output. Pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…CW cryogenic Yb:YAG lasers with CW output power ě400 W have been reported by a number of groups, including 455 W [3], 400 W [129], 550 W [130], 500 W [135], and 494 W [138]. The largest CW power for a Yb:YAG cryogenic laser reported to date, 963 W, was for a Yb:YAG cryogenic oscillator driven double-passed Yb:YAG preamplifier followed by a Yb:YAG power amplifier demonstrated by our group [132]. We include Yb:CaF 2 here due to a recent high power demonstration with a quantum-defect of only 1.11% [134].…”
Section: Cryogenic Cw Lasersmentioning
confidence: 72%
See 1 more Smart Citation
“…CW cryogenic Yb:YAG lasers with CW output power ě400 W have been reported by a number of groups, including 455 W [3], 400 W [129], 550 W [130], 500 W [135], and 494 W [138]. The largest CW power for a Yb:YAG cryogenic laser reported to date, 963 W, was for a Yb:YAG cryogenic oscillator driven double-passed Yb:YAG preamplifier followed by a Yb:YAG power amplifier demonstrated by our group [132]. We include Yb:CaF 2 here due to a recent high power demonstration with a quantum-defect of only 1.11% [134].…”
Section: Cryogenic Cw Lasersmentioning
confidence: 72%
“…We begin by first looking at the evolution of Yb:YAG, Yb:YLF, and Yb:CaF 2 CW cryogenic lasers; Yb:YAG and Yb:YLF materials have been used for the highest power CW demonstrations to date. Figure 44 shows the CW output power obtained from Yb:YAG cryogenically-cooled lasers operating near 80 K. The corresponding data and references are shown in Table 7 [1,3,4,30,108,109,[126][127][128][129][130][131][132][133][134][135][136][137][138][139]. The first CW Yb:YAG demonstration was by Lacovara [1], who reported 40 W output power.…”
Section: Cryogenic Cw Lasersmentioning
confidence: 99%
“…The level scheme becomes an almost four-level minimizing reabsorption, the stimulated cross-section improves by ∼5, while the thermal conductivity increases 2.5 to 4 times depending on the dopant level. 81 However, the emission linewidth and thus, the amplification bandwidths of these systems reduce to typically <1 nm, corresponding to a transform-limited pulse duration of ∼5 ps. A few cryogenically cooled systems have been presented, such as a system generating 287 W average power with 5.5 ps duration pulses corresponding to 3.7 μJ pulse energy.…”
Section: Flashlamp-pumped and Diode-pumpedmentioning
confidence: 99%
“…99 A system with a double-and single-pass amplifier was presented based on multiple thick Yb:YAG disks generating up to 15.2 μJ pulse energy with 760 W average power and 12 ps duration. 81 Another scheme to reduce thermally induced aberrations is a slab amplifier. The beam multipasses through the slab offering lower thermal aberration compared to rod-type designs, high small signal gain as well as a compact design.…”
Section: Flashlamp-pumped and Diode-pumpedmentioning
confidence: 99%
“…On the other hand, Yb:YAG bulk amplifier at cryogenic temperature are available for scaling both energy and average power, combining the good thermo-optical properties of the Yb:YAG crystal and the advantage of high single-pass gain. Cryogenic cooling of the Yb:YAG gain medium [10][11][12] dramatically reduces the saturation fluence (~1.5 J/cm 2 at 77 K). Recently, Hong et al demonstrated a 40 mJ, ps cryogenic Yb:YAG bulk CPA laser system operating at 2 kHz repetition rate [13].…”
Section: Introductionmentioning
confidence: 99%